2003
DOI: 10.1016/s0029-7844(03)00168-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of intracardiac echogenic foci for Down syndrome: a meta-analysis*1

Abstract: Intracardiac echogenic foci increase the risk of Down syndrome five- to seven-fold. This information should be considered in the decision making for amniocentesis in conjunction with the woman's background risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 34 publications
3
33
1
Order By: Relevance
“…This relation was confirmed in multiple studies, however, most of the studies were with women at high risk for aneuploidy [3].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…This relation was confirmed in multiple studies, however, most of the studies were with women at high risk for aneuploidy [3].…”
Section: Introductionmentioning
confidence: 77%
“…In a metaanalysis evaluating the relation of EF with Down syndrome (T21), including 11 studies with a total of 51,831 patients, the authors concluded that the prior risk of Down syndrome (as calculated by maternal age, history of previous affected pregnancy and prior screening tests) is increased by a factor of 5.4 when EF are present and reduced by a factor of 0.8 when no foci are detected [3].…”
Section: Introductionmentioning
confidence: 99%
“…EIFs probably represent a normal variant of papillary muscle development (i.e., calcification). However, many authors have advocated that their presence should be interpreted as an increased risk for aneuploidy [12,13]-in particular Down's syndrome (DS) [9,[14][15][16][17]-or congenital heart disease [10].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis in 2003 reported that 15% to 30% of fetuses with T21 had an EIF, whereas this finding was present in only 4% to 7% of unaffected fetuses. 5 The conclusion was that the presence of an EIF increased the risk of Down syndrome.…”
mentioning
confidence: 99%